PENGARUH MEDIA SOSIAL TERHADAP POLA KOMUNIKASI DAN HUBUNGAN SOSIAL DALAM KALANGAN GENERASI Z - Nayya Efriyani br purba; Nidia Ramadani; Nurul Khotimah; Darmawati; Aulia Mawaddah (Universitas Muhammadiyah Metro, 2026)
This study is a systematic review of the literature aiming to investigate the influence of social media on communication patterns and social relationships among Generation Z. Using the Systematic Literature Review (SLR) method, literature sources were selected from Scopus, DOAJ, and Google Scholar, with a publication period between 2014 and 2025. The analysis reveals that social media has a complex and diverse impact on the interpersonal communication patterns of Generation Z: increased communication frequency, shifts in communication style toward more visual and instant forms, and a decline in face-to-face communication skills. Although negative impacts such as dependency and interference in active listening skills were identified, social media also provides positive impacts including broader global connectivity. These findings are analyzed through the frameworks of Computer-Mediated Communication (CMC), Uses and Gratifications Theory, Social Presence Theory, and Media Richness Theory. The implications of these findings are relevant for Guidance and Counseling (BK) services, particularly in the development of digital literacy programs and prevention of social media addiction among students.